Viewpoints of Veterans Affected by Psychological Disorders towards usage of telemental services for War Veterans - M. Ahmadi; K. Bahaadinbeigy; T. noori (Afarand Scholarly Publishing Institute, 2014)
Background & Purpose: The use of telemedicine in military capabilities, access to specialized medical services, resulting in a continuing care for veterans is possible. This study aimed to investigate psychological warfare point of using mental health systems has been done remotely for war veterans. Methods & Materials: This cross - sectional study was conducted in 2013 A questionnaire was designed and standardized by receiving comments from telemedicine experts and psychiatrist. The researcher personally visited respondents, thus 100% data were collected. Data analysis using 17.0 SPSS software and descriptive statistics were performed. Results: Veterans on the effectiveness and necessity of mental health service use remote stressed. And concerns about access to a computer, provided the drug, the need for further training and active involvement of families. Conclusion: It is clear that the Telemental health is practical solutions to meet the mental health needs of veterans. .In the discussion, such as user training requirements, reliability, confidentiality and other legal policies should be considered. Experiences of other countries indicate the success of this type of service needs assessment, feasibility and planning is correct.